The Feminism Melancholia for the Main Characters of the Novel “Kim Ji-Yeong” - Alfadlilah, Muna (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2025)
Trauma is inseparable from a strong memory matter. The bond between trauma and memory is inseparable so memory will always remember the trauma of an individual. Conflicts in a literature work cause various impacts and are influenced by social, cultural, and psychological factors. One of the factors is an internal family conflict. The conflict may lead to psychological factor impacts due to mental problems, depression, such as melancholia. Melancholia refers to the mental problem expressing the problems about life perception due to depression and a tendency to anxiety, fatigue, desperation, and excessive anxiety. This research aimed to describe the reflection of melancholia of the main characters in the novel titled Kim Jie-Yeong by Cho Nam Joo. The applied theory to analyze the melancholia of the main characters is - Cathy Caruth's theory. This qualitative research applies the literature psychology. The research data consisted of some text units in the novel Kim Ji-Yeong based on the research objective. The data source from the novel of Kim Ji-Yeong. The applied data collection techniques were reading and noting while the data analysis was descriptive. The results found that the situations of the primary characters indicated the suffering of trauma and melancholia in the past events. Keywords: Conflict, Melancholia, Trauma